Kajian Semantik Bahasa Figuratif pada Upacara Adat Perkawinan Tahap Tunda Binna (Peminangan) di Desa Kalembuweri Suku Wewewa Sumba Barat Daya - Kelen, Konradus Doni; Kami, Kanisius; Gena, Angel Bertha H.; Lere, Norbertus (Ideas Publishing, 2024)
This research was initiated with a strong curiosity about the figurative language employed by the Sumba people during the marriage ceremonys proposal stage. The primary objective of this study was to investigate the significance of figurative language in the marriage process. The ethnographic method was used in this study. The findings of this study indicate that the figurative language employed during the proposal stage of the marriage process serves to humble oneself and uphold the dignity of women. Women should never be treated as commodities. The implications of this research can inspire many individuals to respect and honor women.